2021
DOI: 10.1111/aas.13816
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in parturients with an accidental dural puncture: A case‐controlled prospective observational study

Abstract: Background: We set out to examine incidence of chronic headache and back pain in women with PDPH after accidental dural puncture during labor.Methods: Chronic headache, backache, and disability were assessed 18-24 months postpartum. Women with PDPH treated with epidural blood patch (PDPH-EBP) were identified and matched with women who had a PDPH without epidural blood patch (PDPH-no EBP), with women with uncomplicated epidural analgesia and with women without epidural analgesia. Our primary outcome was inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Similar to what was observed by Ranganathan et al (7) and Binyamin et al (25) , we did not observe a difference in the incidence of chronic symptoms in women who had an epidural blood patch compared to those who did not. Webb et al (5) , however, reported a lower incidence of both headache and backache in women who received EBP as compared to those who did not.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to what was observed by Ranganathan et al (7) and Binyamin et al (25) , we did not observe a difference in the incidence of chronic symptoms in women who had an epidural blood patch compared to those who did not. Webb et al (5) , however, reported a lower incidence of both headache and backache in women who received EBP as compared to those who did not.…”
Section: Discussionsupporting
confidence: 91%
“…The management of PDPH in our cohort may have been more conservative than that reported in similar studies. We performed EBP in 41.7% of women who had PDPH, whereas Binyamin et al (25) , Webb et al (5) and Ranganathan et al (7) reported 51.3%, 62.5% and 53.4% respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Accidental dural puncture is the most common complication in obstetric anesthesia, occurring in 0.5%‐1% of all labor epidurals 1 and resulting in a postdural puncture headache (PDPH) in 60%‐70% of these parturients 2 . PDPH is a debilitating condition that can lead to long‐term chronic headache and backache and serious neurological sequelae 3‐6 …”
Section: Introductionmentioning
confidence: 99%
“…Accidental dural puncture (ADP) is a serious complication of obstetric anesthesia 1 2. Although several studies have identified specific risk factors, there remains a need for modifiable etiologies3 4 There has been growing interest in root cause analysis, an exploration of key system-level factors as contributors to the occurrence of accidents 3.…”
Section: Introductionmentioning
confidence: 99%